Three new species of Licania (Chrysobalanaceae) from Peru - Ghillean Prance (PhytoKeys, 2014)
Recent collections received for identification contain three conspicuous new species for the mid altitude forests of Amazonian Peru. Licania palcazuensis, L. apiknae and L. monteagudensis are described as new and their relationship to other species is discussed. A key is provided for all the species of Licania subgenus Licania section Licania known to occur in Peru.